Chemotherapy‐induced oral mucositis and associated infections in a novel organotypic model. (20th February 2018) - Sobue, T.; Bertolini, M.; Thompson, A.; Peterson, D.E.; Diaz, P.I.; Dongari‐Bagtzoglou, A.
Abstract : Oral mucositis is a common side effect of cancer chemotherapy, with significant adverse impact on the delivery of anti‐neoplastic treatment. There is a lack of consensus regarding the role of oral commensal microorganisms in the initiation or progression of mucositis because relevant experimental models are non‐existent. The goal of this study was to develop an in vitro mucosal injury model that mimics chemotherapy‐induced mucositis, where the effect of oral commensals can be studied. A novel organotypic model of chemotherapy‐induced mucositis was developed based on a human oral epithelial cell line and a fibroblast‐embedded collagen matrix. Treatment of organotypic constructs with 5‐fluorouracil (5‐FU) reproduced major histopathologic characteristics of oral mucositis, such as DNA synthesis inhibition, apoptosis and cytoplasmic vacuolation, without compromising the three‐dimensional structure of the multilayer organotypic mucosa. Although structural integrity of the model was preserved, 5‐FU treatment resulted in a widening of epithelial intercellular spaces, characterized by E‐cadherin dissolution from adherens junctions. In a neutrophil transmigration assay we discovered that this treatment facilitated transport of neutrophils through epithelial layers. Moreover, 5‐FU treatment stimulated key proinflammatory cytokines that are associated with the pathogenesis of oral mucositis. 5‐FU treatment of mucosal constructs did not significantly affect fungal or bacterial biofilm growth under the conditions tested in this study; however, it exacerbated the inflammatory response to certain bacterial and fungal commensals. These findings suggest that commensals may play a role in the pathogenesis of oral mucositis by amplifying the proinflammatory signals to mucosa that is injured by cytotoxic chemotherapy.